Plasma BDNF in burnout-related depressive disorders: The mediating role of perceived social isolation and the biopsychological effect of a multimodal inpatient treatment - Roberto La Marca; Monika Scheiwiller; Michael Pfaff; Pearl La Marca-Ghaemmaghami; Heinz Böker (Journal of Affective Disorders Reports)
Background: The neurotrophic hypothesis of depression assumes that a reduced expression of BDNF may partially explain the development of depression, and that antidepressants increase BDNF levels and mood. In this study, we aimed at comparing plasma BDNF levels in inpatients with a burnout-related depressive disorder to those of healthy controls and explore the effects of a multimodal inpatient treatment. Moreover, we examined the mediating role of BDNF and perceived social isolation in predicting depression severity. Methods: Thirty-five inpatients treated at a specialized burnout clinic and 21 matched healthy controls participated in this study. The inpatients responded to self-report questionnaires measuring depression severity, burnout, loneliness, and social isolation as well as a clinician-administered depression questionnaire (HAMD-17) after clinic admission (T1) and before clinic discharge (T2). Plasma BDNF concentrations were determined at the same time points. Inpatients reported on depression severity again at 6 months follow-up (T3). In healthy controls, psychological data and blood samples were collected only once. Results: Inpatients exhibited lower BDNF levels than controls (U = 267.00, p=.045). The treatment led to a significant increase in BDNF levels (z=-1.974, p=.024), whereby the change in BDNF levels and in depression severity were inversely related (HAMD-17: rs=0.30, p=.042). Finally, this association was significantly mediated by perceived social isolation. Conclusions: The findings support the assumptions within the neurotrophic hypothesis and a mediating role of perceived social isolation. Prevention and treatment of clinically relevant burnout and depression should consider perceived social isolation and social integration as an important risk factor and intervention focus, respectively.